ANTIMICROBIAL ACTIVITY OF GREEN TEA FROM GAMBUNG, WEST JAVA, INDONESIA - Daud, Abdurrahman; Shabarni, Gaffar; Riyani, Riyani (Pharmacoscript, 2025)
Gambung green tea (Camellia sinensis var. assamica), cultivated in the highlands of West Java, Indonesia, is renowned for its unique sensory qualities and potential health benefits. Given the growing global concern over antibiotic resistance, there is an urgent need to explore natural alternatives with antimicrobial properties. This study investigated the antimicrobial and antioxidant properties of Gambung green tea extracts against clinically relevant pathogens, including Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, Klebsiella pneumoniae, and Candida albicans. Crude extracts were prepared using water, ethanol, and ethyl acetate, and phytochemical screening revealed the presence of flavonoids, polyphenols, tannins, and anthocyanins. Ethanol extraction yielded the highest extract mass (37.6%) and demonstrated the most potent antimicrobial activity, particularly against S. aureus (IC50 5.0 mg/mL) and S. pyogenes (IC50 7.5 mg/mL). The ethanol extract also exhibited strong antioxidant activity, as measured by the DPPH assay. E. coli showed moderate resistance (IC50 24.34 mg/mL), while K. pneumoniae and C. albicans were less susceptible. The results highlight the potential of Gambung green tea, particularly its ethanolic extract, as a natural antimicrobial and antioxidant agent. Further research is needed to identify specific bioactive compounds and their mechanisms of action. The localized origins and unique environment contribute to the distinctive phytochemical composition and biological activities observed. Further investigation into the specific bioactive compounds and structure-activity relationships is warranted to facilitate the development of Gambung green tea as a natural antimicrobial resource.